“Canada‑Here”: a narrative inquiry into queer international students’ experiences in small‑city Ontario - Dudeja, Mohit (My University, 2026)
This dissertation explores how queer international students negotiate postsecondary education, everyday life, and belonging in small Ontario cities where visibility is heightened, resources can be thin, and “inclusion” is unevenly lived. Grounded in the researcher's positionality as a queer international student, the study is guided by three research questions: How does queerness shape participants’ educational experiences and daily lives?; What institutional and community supports and barriers do they encounter?; and, How do these conditions shape belonging and wellbeing? Drawing on a qualitative narrative inquiry, fourteen in-depth interviews were conducted with queer international students living and studying in small Ontario cities. The transcripts were analysed using a thematic narrative approach. Interpretation was anchored in a combined theoretical framework of intersectionality, identity management theory, and neoliberalism, enabling analysis across structural conditions (such as racialisation, immigration status, institutional governance), everyday communicative labour (such as strategic disclosure, selective silence, embodied self-presentation), and the political economy of international education (such as market logics and uneven support provisioning). Three interrelated themes structure the findings. First, participants narrate “Canada” as an imagined refuge assembled through legal reputation and urban pride imaginaries but recalibrate their imaginings through their small-city experiences, producing a shift from “Canada” to “Canada‑here.” Second, belonging emerges as conditional rather than secured: participants engage in ongoing identity management through strategic (in)visibility across audiences and settings, including transnational audiences and imagined futures of going back home. Third, whiteness operates as a structuring norm across public, institutional, and queer-designated spaces, generating racialised distributions of safety and credibility and a recurring double bind in which spaces rarely hold all aspects of the self. Across themes, the dissertation advances a central claim: rights and inclusion can be visible “on paper” and in institutional messaging, while daily life remains shaped by exposure, racialised dynamics within and beyond queer communities, uneven institutional responsiveness, and migration-related uncertainty. The study contributes conceptually by reframing queer safety as place-specific and infrastructural and practically by identifying implications for small-city postsecondary institutions, local service ecologies, and policy environments that govern international students’ futures. Keywords: queer international students; small-city Ontario, narrative inquiry, intersectionality, neoliberalism, identity management